2013
DOI: 10.1148/rg.331115178
|View full text |Cite
|
Sign up to set email alerts
|

AIRP Best Cases in Radiologic-Pathologic Correlation: Gastritis Cystica Polyposa

Abstract: A 55-year-old man presented to the emergency department with a chief complaint of right-sided chest pain and was found to be severely anemic, requiring multiple blood transfusions. The patient's history was notable for a Billroth II procedure performed 22 years earlier for peptic ulcer disease. The patient was admitted to rule out myocardial infarction and for work-up for severe anemia. The stool specimen was guiac positive, and subsequent upper and lower endoscopy revealed a large, tannish-red polypoid mass a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…CT can show a heterogeneously iso‐ to hypoattenuating intraluminal lesion with multiple small cysts (several millimeters in diameter). The cysts in GCP may differentiate it from gastric adenocarcinoma, but the appearance may be similar to GIST [6]. On EUS, GCP can appear as a polymorphic, homogeneous cystic mass with a minimal solid component within the gastric mucosa [3,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CT can show a heterogeneously iso‐ to hypoattenuating intraluminal lesion with multiple small cysts (several millimeters in diameter). The cysts in GCP may differentiate it from gastric adenocarcinoma, but the appearance may be similar to GIST [6]. On EUS, GCP can appear as a polymorphic, homogeneous cystic mass with a minimal solid component within the gastric mucosa [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have also revealed the possibility of a malignant transformation from GCP, even in an unoperated stomach, but the incidence of malignancy in GCP patients remains unknown [6,10]. Choi et al [4] reported a significantly higher rate of Epstein – Barr virus in cancer tissue with gastritis cystica profunda (31.1%) than in that without gastritis cystica profunda (5.8%), and its possible role as a premalignant factor requires further clarification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation